2021
DOI: 10.1111/mms.12880
|View full text |Cite
|
Sign up to set email alerts
|

Will harbor porpoises (Phocoena phocoena) be deterred by a pinger that cannot be used as a “dinner bell” by seals?

Abstract: A measure proven successful in mitigating harbor porpoise bycatch, is the use of acoustic deterrents, i.e., pingers. However, most pingers are audible to seals. This may lead to seals associating pinger sounds with easily accessible food, leading to increased depredation, damage, and bycatch. In this study we tested if an experimental pinger, emitting sounds over 30 hr ON/OFF cycles, with low frequency components potentially audible to seals only at close distances, would effectively deter harbor porpoises. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 41 publications
1
12
0
Order By: Relevance
“…Promising results of deterrence by the same pinger model as tested here were also reported for the harbor porpoise, Phocoena phocoena (Omeyer et al, 2020; Königson et al, 2021). In our study, however, the reduction in the click train detection probability of franciscanas in the immediate vicinity of the active pinger was almost half of that observed in harbor porpoises in the study by Omeyer et al (2020), 19.4% and 37%, respectively, but it was higher at 100 m from the pinger (15.4% and 8%, respectively), demonstrating that the same pinger can influence species differently.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Promising results of deterrence by the same pinger model as tested here were also reported for the harbor porpoise, Phocoena phocoena (Omeyer et al, 2020; Königson et al, 2021). In our study, however, the reduction in the click train detection probability of franciscanas in the immediate vicinity of the active pinger was almost half of that observed in harbor porpoises in the study by Omeyer et al (2020), 19.4% and 37%, respectively, but it was higher at 100 m from the pinger (15.4% and 8%, respectively), demonstrating that the same pinger can influence species differently.…”
Section: Discussionsupporting
confidence: 80%
“…Considering the duration of the experiment (65 days), we believe this result very promising. Habituation was also not observed in P. phocoena during a 64‐day experiment (Königson et al, 2021) and during eight months of experiments with the same pinger (Omeyer et al, 2020). In contrast, Cox et al (2003), using a theodolite to record bottlenose dolphin surfacing in the vicinity of a Netmark 1000 pinger (Dukane Seacom, Sarasota, FL), observed no significant deterrent effect after only 11 days of study, strongly suggesting that habituation occurred.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…'Seal safe' banana pingers (50-120 kHz) increase avoidance responses in vulnerable Franciscana dolphins, although this effect is fairly small, with 19.4% reductions in surfacing frequency close to the pinger and 15% at 100 m (Paitach et al 2022). Significant reductions of bycatch and increased avoidance behaviour in harbour porpoises continue, adding to the evidence base that pingers are effective for at least some small odontocetes in gillnet fisheries globally (Chladek et al 2020;Omeyer et al 2020;Königson et al 2021).…”
Section: ) and Only Minor Behavioural Responses In Bothmentioning
confidence: 97%
“…Habituation and habitat exclusion are important factors when using sensory technologies. Habituation to sensory deterrents has been recorded in empirical studies (Amano et al 2017), and where it is not observed, this is perhaps due to the long time periods over which it could occur and difficulties in detecting it during short field studies which focus on immediate results (Königson et al 2021). Habitat exclusion has been found in studies and derived in models when investigating some technologies, although evidence of the effects on populations are not clear (van Beest et al 2017).…”
Section: Fig 5 Effective and Ineffective Sensory Deterrent Venn Diagr...mentioning
confidence: 99%